Lived experience: a study of young people said to be missing in Education and Training yet not found in Employment, Kagiso, South Africa - Luxomo, Viwe Gift (My University, 2022)
Non-participation in education, training, and employment (NEET) has become the dominant feature in young people’s lives. At its launch the notion of ‘NEET’ was branded as a possible panacea to the identified as ‘social exclusion’ outcome. In many ways, this idea assisted to reinsert young people in the dominant policy discourse. However, it has not helped to address their social and economic needs. In this doctoral study, I produced substantial descriptions drawn from the qualitative research approaches that focused on the lived experience of the township youth. I explored the perceived possibilities, choices, expectation and meaning the so-called ‘NEETs’ attach to non-participation in education, training, and employment. I made use of interpretative phenomenology to conduct the interviews with the seven young people and fifteen persons in their circles of intimacy. The findings pointed to the outstanding barriers for accessing education, training, and employment; delayed transitions on post-school possibilities; and the constrained transition into employment. I found the construct of symbolic violence to be providing insightful tools for making sense of the wider challenges for accessing opportunity in South Africa, while care helps us to [re]imagine a world (society) that is committed to make the possibilities for human functioning ready-to-hand. These helped me to develop a model for approximating the possibilities that are intended to shift current preoccupation with discourse of skills towards care for humanity. I argued that raising the expectations on what young people must give to their societies, without adequately equipping them to meet the emergent demands, set them up for failure. A study of the youth experiences at a time when non-participation in education, training, and employment is increasing is important and opportunistic for three reasons: It is topical, relevant, and timely.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022